2020
DOI: 10.25304/rlt.v28.2419
|View full text |Cite
|
Sign up to set email alerts
|

A chemistry laboratory platform enhanced with virtual reality for students’ adaptive learning

Abstract: In recent years, virtual reality system (VRS) has become more prominent among many researchers due to its capacity of providing as close as possible to real-life experience for users from diverse fields of life, such as tourism, academics, manufacturing and medicine. In this study, we present an VRS for the titration experiment in a chemistry laboratory to enable students to learn the titration experiment in a virtual laboratory environment before proceeding to the chemistry wet lab. The virtual chemistry labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“… 4 Other research showed improvements in learning outcomes 70 and understanding in practical chemistry classes. 71 In spite of these discrepancies, all these features together justify the growing use of AR in education and research.…”
Section: Results and Analysis Of The Data On Jcr Research On Visualiz...mentioning
confidence: 99%
“… 4 Other research showed improvements in learning outcomes 70 and understanding in practical chemistry classes. 71 In spite of these discrepancies, all these features together justify the growing use of AR in education and research.…”
Section: Results and Analysis Of The Data On Jcr Research On Visualiz...mentioning
confidence: 99%
“…Some articles reviewed VL APPs for use in Biology, Biotechnology and Chemistry classes, and although they reaffirm that VL must not substitute the real experience lab work, the advantages are best seen when VL is combined with traditional lab practices as they indicate good general cognitive effects in the development of skills and motivation (Cataldi and Dominighini, 2018;Sypsas and Kalles, 2018). Comparatively with the same amount of training time, there is a large increase in student achievement when the traditional methodology is combined with the virtual laboratory and tutoring led by the teacher (Agbonifo et al, 2020).…”
Section: Challenges With Vl Environmentsmentioning
confidence: 97%
“…2−9 Specifically for training laboratory skills in titration, VR scenarios have been developed and tested. 10,11 These studies suggest that virtual environments can enhance the learners' confidence when performing chemical experiments, and they can serve as pretraining for real laboratory practice. Similarly, Tee et al 12 have shown that students could also gain confidence when performing experiments using a markerbased AR titration tool.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Emerging technologies, such as virtual reality (VR) and augmented reality (AR), have provided alternative hands-on experience in recent years. In chemical education, both AR and VR have been used to support diverse learning activities. Specifically for training laboratory skills in titration, VR scenarios have been developed and tested. , These studies suggest that virtual environments can enhance the learners’ confidence when performing chemical experiments, and they can serve as pretraining for real laboratory practice. Similarly, Tee et al have shown that students could also gain confidence when performing experiments using a marker-based AR titration tool.…”
Section: Introductionmentioning
confidence: 99%